Connecting Green from Posts to Purchases: Social Media Knowledge Shapes Attitudes and Purchasing Practices - Windy Eka Saputri (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
The increasing emphasis on environmental issues, combined with the growing persuasive effect of social media, has changed the dynamics of consumer engagement, encouraging them to build their knowledge of green products. This paper aims to develop a conceptual model that integrates the KAP (Knowledge-Attitude-Practice) theory with price and green perceived value to examine consumer behavior in the context of social media marketing. Social media marketing provides knowledge stimuli that influence attitude change and intention formation, which, in turn, lead to subsequent purchasing behavior. Practices extend beyond a singular frame of reference, encompassing both first and repeat purchases, thereby extending the KAP cycle and integrating modern marketing. Price as a marketing strategy is considered a moderate boundary condition for purchasing green products. Green perceived value refers to both an attitude reinforcement and a supporter of consumer purchase and repeat-purchase attitudes. The proposed model advances theory by extending the KAP framework in marketing communication to green marketing, providing a practical contribution that enables marketers to refine pricing and value communication. The paper concludes that the proposed model makes a significant contribution to both marketing scholarship and managerial practice, and invites empirical validation across diverse consumer segments.